Effects of Soil Compaction and Water Sress on the Growth Performance of Hopea odorata Roxb. Mimusops elengi Linn. Seedlings -Morphological Responses - Zainudin, Siti Rubiah; Kamis, A (2002)
Soil compaction and its impact on plant growth and yield are issues of global concern (Voorhees, 1991). Compaction increases the bulk density or strength of a soil, commonly referred to as its 'mechanical impedence', and reduces its conductivity, permeability and diffusivity to water and air (Materechera et af., 1991). Compaction of urban soils drastically reduces infiltration rate and consequently encourages runoff losses. In addition, even the little quantity of water that infiltrates the soil is so tightly held in the micropores that plant roots find it difficult to extract. A loose soil, on the other hand, permits infiltration but the water may be lost to the plant through rapid drainage. Therefore in either case (compact or loose soil), plant may suffer moisture stress and reduced growth even though the right amount of water may have been applied. When soil is compacted, the bulk density increases and tQtal porosity decreases. This inhibit plant growth and reduces root elongation (Barley, 1965;· Taylor and Ratliff, 1969) and cause reduction in shoot'-'growth (Schurman, 1965). Field experiments have suggested that soil compaction reduces shoot growth by restricting the volume of soil explored by the root system and hence the availability of water and nutrients to the plant (Bennie and Botha, 1986; Taylor and Brar, 1991). A thorough understanding of the interactive effect of soil compaction and soil moisture regimes is essential for good growth of the plants and their effects were investigated in this study.